MENINGKATKAN PRODUKTIVITAS PRODUKSI PT.TAHU SUMEDANG DENGAN METODE APC - Zaharuddin, Zaharuddin; Fauzi, Muhammad; Utama, Denny Wallady (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
The rapid development of industry and increasingly fierce competition between companies encourage companies to maintain their existence by planning and developing competitive strategies. Increasing efficiency is the key to achieving greater benefits, such as increasing the effectiveness of assets in product development and achieving production targets. Measuring productivity is an important indicator in managing company resources. The Sumedang ABC Tofu Factory, as a home industry, experienced a decline in productivity due to suboptimal use of resources, such as labor, raw materials, energy and capital. The American Productivity Center (APC) method is used to measure productivity and identify factors causing decreased productivity. The measurement results show a decrease in productivity in periods 2 and 3 compared to the base period. Based on the analysis of the productivity index, profitability index, and price improvement index, the improvements needed include saving and monitoring the use of raw materials and energy, as well as reducing less than optimal capital. Companies can implement improvement solutions to increase production productivity and strengthen competitiveness in the market